Phytochemical Screening and Antibacterial Potential Ethanol Extract of Kemangi Leaves (Ocimum basilicum L.) Towards Staphylococcus aureus - Sanjaya, Angga Nugraha; Harahap, Urip; Dalimunthe, Aminah (Publisher Cv. Inara, 2022)
An infectious disease is a disease with the highest prevalence in the world, with a great risk of transmission. Staphylococcus aureus is a pathogen that can cause several infectious diseases. The use of kemangi leaves as vegetables can be used as an invention in treating infections caused by bacteria. The purpose of this study was a phytochemical screening test to determine what metabolites are contained and their potential activity against Staphylococcus aureus. The research method is to carry out a qualitative phytochemical screening test using reagents and an antibacterial potential test against Staphylococcus aureus using the Kirby-Bauer method (diffusion agar) with varying concentrations. The results showed that kemangi leaves extract showed positive results on the secondary metabolite compounds, were alkaloids, flavonoids, saponins, tannins, glycosides, and steroids/triterpenoids. The diameter of the inhibition zone at a concentration of 500 mg/mL showed the diameter of the inhibition zone was 11.93 ± 0.25 mm with the strong category group. The conclusion is that the ethanolic extract of kemangi leaves shows the ethanolic extract of kemangi leaves has potential as an antibacterial.